The Tajweed Competencies of TPQ Teachers and Their Influence on BTQ Learning Outcomes - Fitria Sartika; Mahyudin Ritonga; Desyanti Desyanti (Institut Agama Islam Negeri Imam Bonjol Padang, 2021)
This study was motivated by the importance of Tajweed to be mastered by a Muslim in learning and reciting the Qur'an, especially for TPQ teachers. However, based on certification test results, the Tajweed competencies of TPQ teachers were very diverse. Based on this reality, researchers had the interest to conduct an in-depth study on Tajweed competencies of TPQ teachers and their influence on BTQ learning outcomes. This study aimed to find out Tajweed competencies of TPQ teachers and their influence on BTQ learning outcomes in TPQ. This study used qualitative and quantitative approaches (mixed methods). The study was conducted on 7 TPQ teachers and heads as well as 20 TPQ students in Lamposi Tigo Nagari Sub-District Payakumbuh City West Sumatra. Data were collected through interviews, observation, documentation study, and written tests. Data were analyzed using qualitative analysis, namely data reduction, data display, and conclusion drawing, as well as quantitative analysis on BTQ learning outcomes in TPQ using Microsoft Excel 2007. Based on the results, firstly, practically, all TPQ teachers in Latina Payakumbuh City. mastered the Tajweed, but theoretically, not all TPQ teachers understood certain terms and rules. Second, BTQ learning activities were not evaluated in a clear and measurable manner. Third, BTQ learning outcomes showed the insignificant influence of the Tajweed competencies on BTQ learning outcomes. The Tajweed competencies of TPQ teachers only had a 19.38% influence on BTQ learning outcomes, while the remaining 80.62% was influenced by other factors